The corrections - Franzen, Jonathan, author 227217 (New York : Farrar, Straus and Giroux, 2001)
The Corrections is a 2001 novel by American author Jonathan Franzen. It revolves around the troubles of an elderly Midwestern couple and their three adult children, tracing their lives from the mid-20th century to "one last Christmas" together near the turn of the millennium. The novel was awarded the National Book Award in 2001[1] and the James Tait Black Memorial Prize in 2002.